2014
DOI: 10.7150/ijms.8895
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Culture Environment Increases the Efficacy of Platelet Rich Plasma Releasate in Prompting Skin Fibroblast Differentiation and Extracellular Matrix Formation

Abstract: Platelet rich plasma clot- releasate (PRCR) shows significant influence on tissue regeneration in clinical trials. Although, the mechanism of PRCR effect on fibroblast differentiation has been studied on 2D culture system, a detailed investigation is needed to establish the role of PRCR in cell seeded in 3D scaffolds. Therefore, a study was conducted to evaluate the influence of PRCR in fibroblasts (DFB) differentiation and extracellular matrix formation on both 3D and 2D culture systems. Cell viability was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
14
0
2
Order By: Relevance
“…To date, there have been reports that 3D environments promote stem cell differentiation into ECs, 58 cardiomyocytes, 8 fibroblasts, 47 smooth muscle cells, 39,53 and other lineages. 9,31,41,46,51 Our finding that 3D biomaterials are potent modulators of endothelial specification concurs with Zhang et al that demonstrated a significant improvement of endothelial differentiation 3D fibrin (45% efficiency), compared to 2D (10% efficiency) substrates.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been reports that 3D environments promote stem cell differentiation into ECs, 58 cardiomyocytes, 8 fibroblasts, 47 smooth muscle cells, 39,53 and other lineages. 9,31,41,46,51 Our finding that 3D biomaterials are potent modulators of endothelial specification concurs with Zhang et al that demonstrated a significant improvement of endothelial differentiation 3D fibrin (45% efficiency), compared to 2D (10% efficiency) substrates.…”
Section: Discussionmentioning
confidence: 99%
“…PRP has previously been shown to stimulate both fibroblast proliferation and human fibroblast‐populated collagen gel contraction (Caceres, Martinez, Martinez, & Smith, ). Moreover, platelet releasate has been shown to increase proliferation and differentiation, where TGF‐β1 has been speculated to be the key factor in platelet releasate affecting fibroblastic differentiation (Rothan et al, ). To our knowledge, this is the first study to show more pronounced effects of SR on HDF's proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a conventional 2D monolayer cell culture, the 3D culture system had advantages in that it can mimic the structural architecture and different function of the tumor tissues (Weiswald et al, 2015;Rothan et al, 2014). It is well known that cellcell interactions and cell-matrix interactions within a 3D environment are important to the physiological function and response of cancer cells to anticancer agents Tsunoda et al, 2014;Akeda et al, 2009).…”
Section: Discussionmentioning
confidence: 99%